Neolithic structure (Area A) (Scottish Historical and Archaeological Internet Reports, 2011)
All the evidence for Neolithic activity is presented in this chapter. The timber structure is described under the following headings: terminals, side walls, internal structural elements, internal features and external features, and possible interpretations are presented. There are specialist sections on radiocarbon dates, prehistoric pottery (including a single Iron Age sherd), fired clay, bone and charred plant remains. The discussion considers the evidence for a single structure or separate structures, function and destruction.